2019
DOI: 10.1002/we.2381
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the impacts of passive and semiactive structural control on a fixed bottom and a floating offshore wind turbine

Abstract: The application of structural control to offshore wind turbines (OWTs) using tuned mass dampers (TMDs) has shown to be effective in reducing the system loads. The parameters of a magnetorheological (MR) damper modeled by the Bouc‐Wen model are modified to utilize it as a damping device of the TMD. Rather than showcasing the intricate design policy, this research focuses on the availability of the MR damper model on TMDs and its significance on structural control. The impact of passive and semiactive (S‐A) TMDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Nevertheless, the authors also showed that the control performance is highly sensitive to the damper's time lag. Semi-active MR dampers also improved the response of the undamped side-to-side motion due to misaligned wind and waves [154]. Caterino carried out an experimental analysis studying the performance of the MR damper.…”
Section: Semi-active Vibration Methodsmentioning
confidence: 99%
“…Nevertheless, the authors also showed that the control performance is highly sensitive to the damper's time lag. Semi-active MR dampers also improved the response of the undamped side-to-side motion due to misaligned wind and waves [154]. Caterino carried out an experimental analysis studying the performance of the MR damper.…”
Section: Semi-active Vibration Methodsmentioning
confidence: 99%
“…The pendulum TMD modelled in the TMD module can be utilised as a passive device with constant parameters or semiactively in which the damping force can be controlled. 12 In this study, the TMD module in…”
Section: Implementation Of Ibas In Openfastmentioning
confidence: 99%
“…Beyond a single passive TMD, Zuo et al 10 investigated the effect of multiple TMDs on a finite-element monopile turbine model written in ABAQUS ® ; Sun 11 also investigated the vibration suppression of a monopile turbine using a semiactive TMD under multi-hazards. Furthermore, Park et al 12 included a single pendulum TMD in FAST, which can oscillate omni-directionally (i.e., 2-D motion) with different semi-active control strategy.…”
mentioning
confidence: 99%
“…The analytical formulas of a blade-TMD designed by ESM GmBH are established in this Section (Park et al, 2019). The blade-TMD is mounted inside a blade, and consists of a universal joint, dampers, a mass, an elastomeric end-stop spring, and a regulation spring system as shown in Figure 2.…”
Section: Wind Turbine Models and Simulation Toolsmentioning
confidence: 99%